Municipal tourism management and sustainable development: Evidence from Huánuco, Peru - Villena-Andrade, Tomas Dali; Espejo-Simenon, Soto; Leonardo-Beltrán, Carlos Dante; Bravo-Taboada, Yossary Darill; Guanilo-Luna, Ulises Renieer (Edelweiss Applied Science and Technology, 2025)
Tourism has become a strategic axis for local development in Latin America, combining economic growth, cultural preservation, and social inclusion. In this context, municipal governments play a decisive role in managing tourism as a multidimensional activity that requires planning, coordination, and sustainability-oriented policies. This study analyzed the relationship between municipal tourism management and the sustainable development of tourism in the district of Huánuco, Peru. The research followed a basic approach with a descriptive–correlational scope and a non-experimental cross-sectional design. The population consisted of 384 visitors, 48 tourism enterprises, and the staff of the municipal sub-management of tourism, with data collected through structured surveys and semi-structured interviews. The reliability of the instruments was confirmed with a Cronbach’s alpha of 0.861, indicating high internal consistency. The results revealed a moderate and positive association between municipal management and sustainable tourism development. Visitor-oriented and public-activity-oriented management showed weak correlations, highlighting persistent gaps in infrastructure, promotion, and institutional coordination. In contrast, internal municipal management displayed a stronger association, underlining the importance of governance capacity, leadership, and planning. Furthermore, social sustainability emerged as the most valued dimension, particularly in terms of community well-being and cultural identity, while economic sustainability was rated the lowest, reflecting weak competitiveness and limited recognition of the “Huánuco Brand.” These findings emphasize that municipalities must reinforce their leadership role through inclusive strategies, participatory governance, and targeted investments, ensuring that tourism becomes a long-term driver of economic, social, and cultural sustainability in the region.